2021
DOI: 10.1002/cplu.202100278
|View full text |Cite
|
Sign up to set email alerts
|

A Highly‐Efficient Oxygen Evolution Electrocatalyst Derived from a Metal‐Organic Framework and Ketjenblack Carbon Material

Abstract: The composite of the metal‐organic framework (MOF) Ni(Fe)‐MOF‐74 and the highly conductive carbon material ketjenblack (KB) could be easily obtained from the in‐situ MOF synthesis in a one‐step solvothermal reaction. The composite material features a remarkable electrochemical oxygen evolution reaction (OER) performance where the overpotential at 10 mA/cm2 and the current density at 1.7 VRHE are recorded as 0.274 VRHE and 650 mA/cm2, respectively, in 1 mol/L KOH. In particular, the activation of nickel‐iron cl… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

2
23
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7
1

Relationship

2
6

Authors

Journals

citations
Cited by 18 publications
(25 citation statements)
references
References 80 publications
(151 reference statements)
2
23
0
Order By: Relevance
“…The bimodal pore size distribution of Ni 10 Co-BTC/KB with maxima at ~2 nm and ~4 nm reflects the contributions from the MOF and KB. Consequently, the BET surface area and pore volume of the Ni 10 Co-BTC/KB composite with 596 m 2 /g and 0.45 cm 3 /g, respectively, are higher than the surface area and pore volume of neat Ni 10 Co-BTC (303 m 2 /g, 0.15 cm 3 /g) but still lower than the calculated BET surface area (670 m 2 /g) as determined from the sum of the mass-weighted S(BET) of KB (33 wt.%) and MOF (67 wt.%) (Equation (3) [34]):…”
Section: Synthesis and Characterization Of The Ni-btc Analogsmentioning
confidence: 70%
See 2 more Smart Citations
“…The bimodal pore size distribution of Ni 10 Co-BTC/KB with maxima at ~2 nm and ~4 nm reflects the contributions from the MOF and KB. Consequently, the BET surface area and pore volume of the Ni 10 Co-BTC/KB composite with 596 m 2 /g and 0.45 cm 3 /g, respectively, are higher than the surface area and pore volume of neat Ni 10 Co-BTC (303 m 2 /g, 0.15 cm 3 /g) but still lower than the calculated BET surface area (670 m 2 /g) as determined from the sum of the mass-weighted S(BET) of KB (33 wt.%) and MOF (67 wt.%) (Equation (3) [34]):…”
Section: Synthesis and Characterization Of The Ni-btc Analogsmentioning
confidence: 70%
“…MOFs have been investigated as electrocatalysts due to their high porosity, large surface areas, diversity of composition and structure [27,[30][31][32][33]. MOFs can be used directly for electrocatalytic reactions, but they have drawbacks like (i) low electrical conductivity, (ii) mass transport problems of reactants, products and electrolyte ions through their micropores, (iii) lack of stability especially in highly acidic or alkaline aqueous environments [34]. Because of those drawbacks, MOFs are often employed as precursors or sacrificial agents to construct structured carbon-based metal oxide materials as efficient electrocatalysts [27,32,35].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…Metal-organic frameworks (MOFs) [ 1 , 2 , 3 , 4 ] are potentially porous and mostly crystalline three-dimensional solids, which attract considerable attention in a wide range of envisioned applications [ 5 ], e.g., in catalysis [ 6 ], hydrogen storage [ 7 ], separations [ 8 ], as sensors [ 9 , 10 , 11 ], for nanocluster formation [ 12 , 13 ], or precursors for electrocatalysts [ 12 , 14 , 15 ]. Open metal sites (OMSs), also named coordinatively unsaturated metal sites (CUSs), at the metal center possess a crucial role in some applications [ 16 , 17 , 18 ].…”
Section: Introductionmentioning
confidence: 99%
“…Currently, there are various reports about MOFs and nanoparticles with Ketjenblack carbon which were used as catalysts for OER. [34,37,45,46,47,48] For instance, Sondermann et al [37] showed that the bimetallic Ni10Co-BTC/KB composite gave an overpotential of 344 mV at a current density of 10 mA cm -2 and a Tafel slope of 47 mV dec -1 in 1 mol L -1 KOH. Öztürk et al [48] reported Ni(Fe)-MOF-74 with KB for OER in an alkaline media.…”
Section: Introductionmentioning
confidence: 99%